COMBINATION OF CONSERVATIVE AND SURGICAL TREATMENT OF REFRACTORY GASTROESOPHAGEAL REFLUX DISEASE - NATALIA B. Gubergrits; PAVEL G. Fomenko; NADEZHDA V. Belyaeva (Фундаментальная и клиническая медицина)
Here we analyze the recent data on the prevalence of gastroesophageal reflux disease (GERD), the efficacy of conservative therapy, and main indications for surgery. We further discuss the clinicopathological features, extraesophageal signs and symptoms, and refractory GERD. To consider the efficacy of the personalized approach and longterm administration of proton pump inhibitors, we describe the case report of the patient suffering from refractory GERD with extraesophageal symptoms who underwent anti-reflux surgery.